Il tempo per pensare Un bene essenziale per la comunità universitaria - D'Addario, Silvia; Casalini, Brunella (Comitato Unico di Garanzia, 2019)
This volume collects the proceedings of the seminar organized by the Unique Guarantee Committee for Equal Opportunities of the University of Florence, which focuses on a collective discussion regarding work, study and research conditions in contemporary universities. Drawing inspiration from the reflections of two Canadian teachers, M. Berg and B.K. Seeber, on the feelings of frustration and inadequacy due to the rhythms and objectives sometimes imposed in the university context, this volume focuses on the experiences and moods of all the people involved in the academic community with regard to the obstacles linked to lack of time and economic resources and to increasing workloads. It also offers a reflection on how to create relationships and networks, inaugurate sharing experiments on research and teaching experiences, as well as good practices to contrast those individual and collective drifts which may result in organizational discomfort, thus severely damaging the pursuit for the core values of public universities.